Water quality and risk assessment for the population of Pedro Versiani District, Minas Gerais, Brazil, over the years - Rodrigues, Jairo Lisboa; Alexandrino, Carlos Henrique; Bomfeti, Cleide Aparecida Bomfeti; Lyra, Franciny Xavier Metzker; Corrêa, Luís Ricardo de Souza (Revista Vozes dos Vales: Publicações Acadêmicas, 2021)
Water can be a vector for the transmission of waterborne diseases, which may originate from excreta and living or dead animal Water can represent an important vehicle for the transmission of water diseases, which can originate from human and animal excreta, or even the presence of chemical substances harmful to living beings. The Todos os Santos River, one of the main rivers of the Mucuri basin, supplies water for daily use to the district of Pedro Versiani. It is of great socioeconomic importance for the local population as a large part of this population consumes water from this river untreated. In view of the current scenario in which the Todos os Santos River is located and its importance for the district of Pedro Versiani, the objective of this study was to analyze the water quality of this river by evaluating the chemical, physicochemical, and microbiological parameters by using the water samples from this river in 2012, 2015, and 2018. It was observed that the parameters of coliforms and turbidity do not comply with the standards specified by the current legislation, as well as the concentrations of aluminum and iron. We conclude that the population living around this river is at risk of contracting diseases by consuming water from this river without treatment.
Keywords: daily water intake; Todos os Santos River; water river quality